Inhibition zone test of extract of white sea cucumber (Holothuria scabra) mentawai against Streptococcus sanguinis: Uji zona hambat ekstrak teripang putih (Holothuria scabra) Mentawai terhadap Streptococcus sanguinis - Utmi Arma; Abu Bakar; Kornialia; Fitria Mailiza,; Nabila Soraya Ulfa (Makassar Dental Journal PDGI Makassar, 2024)
Mentawai white sea cucumber (Holothuria scabra) is one of the benthic fauna that can be used as a natural antibacterial treatment. White sea cucumber contains saponin, alkaloid and terpenoid compounds that have antibacterial effects. This study was conducted to determine the antibacterial effect of ethanol extract of Mentawai white sea cucumber against Streptococcus sanguinis, and to determine the concentration of ETP extract that is effective in inhibiting S.sanguinis which was carried out in a laboratory experimental with a posttest only control group design. The extract was made using maceration extraction method. The inhibition zone test method used disc diffusion with 5 samples in each treatment group. The samples consisted of 5 treatment groups, namely 6%, 8%, 10% ETP extract; positive control chlorhexidine 0.2% and negative control ethanol 96%. Data analysis used independent t-test. The results showed that 6%, 8% ETP extract had no inhibition zone but 10% had an inhibition zone of 0.97 mm, 0.2% chlorhexidine of 5.164 mm and 96% ethanol had no inhibition zone. It is concluded that 10% mentawai ATP extract has an antibacterial effect against S.sanguinis but in the weak category and less effective at 0.2% chlorhexidine.